The Peak of the PQRST and the Trajectory Path of Each Cycle of the ECG 12-Lead Wave - Sabar Setiawidayat; Djanggan Sargowo; Setyawan P. Sakti; Sri Andarini (Institute of Advanced Engineering and Science, 2016)
The objective of this present article is to describe the record of the ECG 12-lead examination in order to obtain the peaks of the P, Q, R, S and T from each cycle and also to present the Peak of the PQRST and the trajectory path of each cycle of the ECG 12- lead wave. The duration of the peak R to another is used as the period of each cycle, while the Phytagoras theorem is employed to count the trajectory path of the wave in each step. The Peak PQRST is utilized to diagnose the heart condition, and the trajectory path is the distance taken up by the impulses in the heart muscles. The discrete data from the MIT-BIH and the results of the measurement itself are employed as the data to obtain the values of the peak PQRST and the trajectory path of the wave of each cycle.